Experimental Study on Axial Compression Performance of Thin-Walled Steel Tube Lightweight Concrete Columns With Composite Section - Li, Yue; Yan, Yong; Meng, Xue; Zhang, Kechao; Li, Xiaorun; Gao, Chongming (Frontiers in Materials, 2022)
To provide references for the use of fabricated thin-walled cold-formed steel tubular lightweight concrete columns, the axial compression tests were conducted on single-limb and double-limb specimens. The results were compared with hollow specimens to analyze the effects of the cross-sectional size of the members, wall thickness, and steel ratio of the sections on the axial load-bearing capacity of the specimens. The test results show the following: 1) under the axial load, the typical damage of the specimens is local buckling of the steel tube and local crushing of the concrete. 2) The ultimate bearing capacity of the double-limb specimen is the highest. For the specimen with the sectional height-width ratio of 1.43, the ultimate bearing capacity of the double-limb specimen is 275.71% higher than that of the hollow steel tubular column and 241.49% that of single-limb specimens. 3) Based on the material superposition strength theory, the calculating method of the axial load-bearing capacity of thin-walled cold-formed steel tubular lightweight concrete columns was proposed and verified by comparing with the test results, which provides the design guidance for such members.